1997
DOI: 10.1002/hlca.19970800309
|View full text |Cite
|
Sign up to set email alerts
|

Photoreduction of Triplet Benzophenone by Tertiary Amines: Amine molecular structure and ketyl radical yield

Abstract: Dedicated to Professor Fabian Gerson on the occasion of his retirement, in grateful appreciation of his contributions to science and to education (3.11.97)The photoreduction of triplet benzophenone by 14 tertiary amines was investigated. The ketyl radical yields do not correlate with the quenching rate constants, nor with the electron donor propensity of the amines. Individual structural features of the amines seem to determine the photoreduction yields.Introduction. -The photoreduction of triplet benzophenone… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
32
0

Year Published

1998
1998
2013
2013

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(32 citation statements)
references
References 21 publications
0
32
0
Order By: Relevance
“…Likewise, in accordance with the role of amine radical cation deprotonation, is the fact that, of the two further tertiary amines, iPr 3 N causes a somewhat slower accumulation (the conformation of the radical cation is known to be less favorable for deprotonation) [4850], and DABCO (for which deprotonation is impossible [5152]) causes no detectable formation of TCB •− . Indeed, previous laser flash photolysis experiments had shown that DABCO formed the TCB radical anion on the nanosecond time scale just as the other tertiary amines [53].…”
Section: Discussionmentioning
confidence: 98%
“…Likewise, in accordance with the role of amine radical cation deprotonation, is the fact that, of the two further tertiary amines, iPr 3 N causes a somewhat slower accumulation (the conformation of the radical cation is known to be less favorable for deprotonation) [4850], and DABCO (for which deprotonation is impossible [5152]) causes no detectable formation of TCB •− . Indeed, previous laser flash photolysis experiments had shown that DABCO formed the TCB radical anion on the nanosecond time scale just as the other tertiary amines [53].…”
Section: Discussionmentioning
confidence: 98%
“…While a 'direct' hydrogen abstraction competes in some cases, 1 the dominant photochemical process is assumed to involve electron transfer in the case of ketones. [2][3][4] The primary radical ion pair may undergo proton transfer or back electron transfer which results in an overall hydrogen transfer or deactivation, respectively. In support of this mechanism, quenching rate constants generally increase with decreasing ionization potential of the quencher and increasing solvent polarity unless specific solvation, 3,5,6 steric 4 or stereoelectronic effects 7,8 operate.…”
Section: Introductionmentioning
confidence: 99%
“…Methyl trimethylacetate (6) and butyl isovalerate (9) were chosen to represent poly(tert-butyl acrylate) and poly(n-butyl acrylate), respectively. Hydrocarbons 2,2-dimethylbutane (7) and trans-3-hexene (8) Benzophenone (ca 4 mg) was dissolved in 6 mL of an approximately 90 mM solution of model compound (1)(2)(3)(4)(5)(6)(7)(8)(9) in CD 3 CN. The solution was transferred to a quartz tube capable of being inserted into a standard NMR tube, and inert gas was bubbled through the solution for 5 min to remove oxygen.…”
Section: Methodsmentioning
confidence: 99%